Roots and Ranges: A Detailed Analysis of Plant Distribution Across Diverse Habitats - Zakir Hussain Mir; Irshad Ahmad Wani (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Plant distribution is governed by a complex interplay of environmental, biological, and anthropogenic factors. Understanding how plant species are spread across different habitats—from tropical rainforests to arid deserts offers insights into ecological balance, conservation strategies, and climate change responses. This paper analyzes plant distribution patterns across various ecosystems, explores the factors influencing these patterns, and highlights the significance of biodiversity in maintaining ecosystem health. The study integrates case studies, spatial analysis, and recent research to present a comprehensive overview of global plant dispersion and the challenges posed by habitat alteration.